The phytoremediation of manganese in Gumuskoy (Kutahya, Turkiye) mining soils by the native plants - Konakci, Nevin; Sasmaz, Ahmet (Polish Soc Ecological Engineering-Ptie, 2025)
Manganese (Mn) is one of the most critical elements in the environment and is expected to become an even more important metal in the future due to its widespread use. This study examined the Mn uptake and translocation in 11 different plant species growing in mining soils in Gumuskoy, Turkiye. Plants were washed, dried, and burned at 300 degrees C for 24 h in a drying oven. The Mn contents in plant samples and soil taken from the mining area were analyzed using an inductively coupled plasma mass spectrometer (ICP-MS). Average Mn concentrations in the shoots, roots, and soil of these plants were 1.037, 1.153 and 2.063 ppm, respectively. Based on their ECS and ECR values, Anchusa arvensis, Verbascum thapsus, Silene compacta, Phlomis sp. and Glaucium flavum, were the best accumulators (ECR and ECS > 1). Onosma sp. was a good accumulator (ECR and ECS are close to 1), and Alyssum saxatile, Centaurea cyanus, Carduus nutans, Cynoglossum officinale, and Isatis were less effective accumulators (ECR and ECS < 1). Those plants with ECR/ECS >1 should be subjected to further studies involving the phytore-mediation of Mn-polluted soils.
Keywords: mining area; accumulation; enrichment coefficient; ICP-MS